Попередні відомості про сумчасті гриби на Acer negundo L. в Україні - Дука, А.В.; Коган, С.В.; Duka, A.; Kohan, S. (Інститут екології Карпат НАН України, 2021)
Based on the revision of the specimens in the Scientific Mycological Herbarium CWU (Myc) and own collections, a preliminary list of sac fungi developing on Acer negundo L. in Ukraine has been prepared and analyzed
Preliminary data about Ascomycota representatives on Acer negundo L. in Ukraine
Keywords: гриби; інвазивні види; клен ясенелистий; біорізноманіття